(untitled) (Archive of Conferences, 2021)
The article emphasizes the benefits of teaching foreign languages from an early age and its importance in the development of children, the growth of their worldview, becoming a scientific, intelligent, broad-minded, relevant specialist for society and the state. Also, the organization of interesting, useful and effective lessons for teaching foreign languages in preschool education institutions serves as a basis for training students to be multilingual, broad-minded, able to perform several tasks simultaneously.